Profile of First Time Seizure in Infants with 1 to 12 Months of Age Presenting to a Tertiary Care Pediatric Hospital - Qadri, Ishtiyaq; Bhat, Abdus Sami; Hussain, Wani Shahid; Kakroo, Ayaz Ahmad (Journal of Pediatric Neurology, 2017)
The incidence of seizure in first year of life is very high. Considerable research on neonatal seizures has been done; however information regarding the profile of patients with first time seizure in the age group of 1 to 12 months is scarce. Our study was a prospective observational study undertaken at a tertiary pediatric care hospital in north India with objectives of finding the epidemiological, clinical, and aetiological profile of patients in the age group of 1 to 12 months presenting with first time seizure and to ascertain their electroencephalography (EEG) and imaging findings. Seizure recurrence and developmental delay was also studied during the first six months post seizure. Fifty patients were included in the study. There were 31 male patients (62%) and 19 female patients (38%). Mean age at seizure occurrence was 5.3 ±2.1 months. Forty one patients (82%) presented with generalized tonic seizures. Only two patients (4%) had focal seizures. Seizures in 7 patients (14%) could not be classified. Electroencephalography and brain imaging were done in 42 patients as indicated. Among these 42 patients, EEG abnormalities were noted in 15 patients (35.7%), while imaging abnormalities were noted in 10 patients (23%). Fifteen patients (35.7%) were found to have developmental delay on follow-up. 16 (38%) patients developed recurrence of seizures. Statistical analysis revealed significant association between abnormal imaging and developmental delay at six months and seizure recurrence within six months of first seizure, however the association with abnormal EEG was not statistically significant.
Keywords: infant seizures; developmental delay; seizure recurrence; EEG; imaging